2020
DOI: 10.1016/j.ijscr.2020.11.108
|View full text |Cite
|
Sign up to set email alerts
|

Morel-Lavallée lesion as an unusual cause of hemorrhagic shock: Case report and review of literature

Abstract: Introduction Morel-Lavallée syndrome (MLS) is considered as a rare entity and hemorrhagic shock as a complication is uncommon. Presentation of case We report the case of a 56-year- old man who presented to the emergency department after a road traffic accident. Initially, the patient was hemodynamically unstable (heart rate 160 beats/min and blood pressure 65/30). Physical examination revealed multiple lacerations on his back and a gradually expanding large subcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…1 Interestingly, there have been two case reports of MLLs that have presented to the ED as hypovolemic shock. 12,13 In chronic ML lesions, patient may present with gradually increasing swelling with or without pain and no obvious overlying dermal injury from the initial event. 2,3,7 Diagnostic imaging is key in the confirmation of suspected MLLs.…”
Section: Discussionmentioning
confidence: 99%
“…1 Interestingly, there have been two case reports of MLLs that have presented to the ED as hypovolemic shock. 12,13 In chronic ML lesions, patient may present with gradually increasing swelling with or without pain and no obvious overlying dermal injury from the initial event. 2,3,7 Diagnostic imaging is key in the confirmation of suspected MLLs.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature failed to find a similar report of such extent. However, Daghmouri et al reported a case of extensive MLL involving the lumbar spine and lower limbs, which complicated the patient’s condition and resulted in hemorrhagic shock [ 8 ]. Gummalla et al also reported a case of extensive MLL which was missed on initial evaluation in a patient with a wrist fracture and abrasions over the trochanteric region.…”
Section: Discussionmentioning
confidence: 99%
“…• In the absence of a specific guideline/protocol for the management of soft tissue compartment bleeding, treatment should be individualized based on the hemodynamic status of the patient. Hefny et al [6] Extensive hematoma between the subcutaneous fat and the paraspinal muscles in the back Percutaneous suction drain Discharged Yumoto et al [7] Large hematoma in the lower back with lumbar vertebrae fractures with active contrast extravasation at multiple sites located close to the bilateral lumbar and internal iliac arteries Gel foam embolization Discharged Mao et al [8] Left flank to thigh NOM but later required open drainage for infected collection Discharged Claassen et al [9] Lower lumbar region in the back NOM Discharged Daghmouri et al [10] Lumbar region extending to hips and both legs Surgical drainage Discharged NOM, nonoperative management.…”
Section: Learning Pointsmentioning
confidence: 99%